Motivating creativity: The effects of sequential and simultaneous learning and performance achievement goals on product novelty and usefulness - Miron-Spektor, Ella; Beenen, Gerard (Organizational behavior and human decision processes, 2015)
•We test the effects of learning and performance achievement goals on product novelty and usefulness.•Cognitive flexibility mediated the effect of a learning achievement goal on novelty.•Cognitive closure mediated the effect of a performance achievement goal on usefulness.•Simultaneous learning and performance achievement goals improved product novelty and usefulness more than sequential goals.•The benefits of simultaneous goals were mitigated at high levels of negative affect. Today’s organizations must foster conditions that motivate employees to develop creative solutions that are both novel and useful. Yet product novelty and usefulness have been characterized by distinct, mutually exclusive motivational processes. We test theory on how learning and performance achievement goals can motivate individuals to develop products that are both novel and useful. In an experimental study (n=189) using a product development task, a learning achievement goal enhanced novelty by increasing cognitive flexibility. A performance achievement goal enhanced usefulness by increasing cognitive closure. Furthermore, simultaneous inducement of learning and performance goals enhanced novelty and usefulness more than sequential inducement of each goal. Cognitive flexibility and closure mediated the effects of simultaneous goals on both creativity dimensions, with too much cognitive closure thwarting product novelty. The benefits of simultaneous over sequential goals were mitigated when individuals experienced negative affect. Implications for creativity in organizational settings are discussed.